2013
DOI: 10.1002/app.39995
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of γ‐irradiated microbial cellulose results in bioresorbable, highly conformable biomaterial

Abstract: Conformability to tissues and adequate mechanical strength are clinically useful properties of resorbable biomaterials used in soft tissue repair. Microbially derived cellulose is attractive as a high strength, highly conformable, and biocompatible material for tissue repair, but is not naturally resorbable. Here we show that controlled oxidation of microbial cellulose sheets that have been preirradiated with c-radiation results in a resorbable and fully conformable membrane that can be rapidly rehydrated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…With the pre-γ-irradiation and sodium periodate oxidation treatments on BC membranes, it was reported that in vitro degradation of oxidized BC involved two major phases, (1) initial rapid degradation of about 70-80% of the entire sample; (2) slower degradation of an additional 5-10% which eventually levels off leaving a small amount of nonresorbable material. Further experiments on in vivo degradation (male New Zealand White rabbits) showed the marked degradation of oxidized BC membranes at all-time points, with the most rapid degradation occurring in the first 2-4 weeks [38]. As discussed previously, the absence of enzymes in vivo system makes the cellulose degradation approximately negligible.…”
Section: Biodegradabilitysupporting
confidence: 58%
“…With the pre-γ-irradiation and sodium periodate oxidation treatments on BC membranes, it was reported that in vitro degradation of oxidized BC involved two major phases, (1) initial rapid degradation of about 70-80% of the entire sample; (2) slower degradation of an additional 5-10% which eventually levels off leaving a small amount of nonresorbable material. Further experiments on in vivo degradation (male New Zealand White rabbits) showed the marked degradation of oxidized BC membranes at all-time points, with the most rapid degradation occurring in the first 2-4 weeks [38]. As discussed previously, the absence of enzymes in vivo system makes the cellulose degradation approximately negligible.…”
Section: Biodegradabilitysupporting
confidence: 58%
“…Li et al [ 40 ] reported that amorphous regions of BC chemically modified by periodate oxidation were converted to biodegradable 2,3-dialdehydebacterial cellulose (DABC). Czaja et al [ 41 , 42 ] noted that BC membranes pre-irradiated with γ-radiation and by periodate oxidation degraded most rapidly during the first 2–4 weeks. Hu and Catchmark [ 43 ] suggested that biodegradability could be enhanced by incorporating cellulose-degrading enzymes into the nanostructure of BC.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, many attempts have been made to enhance the degradability of cellulose products in vivo , such as periodate oxidation to introduce 2,3-dialdehyde groups in the nanocellulose chain, 153 enzymatic degradation using the synergistic effect of nanocomplexed exoglucanase 150 and free endoglucanase, and irradiation with γ-radiation to enhance the degradation rate. 154 On the other hand, nonbiodegradable cellulose could be used as a durable supportive material in applications such as cartilage meniscus implants, bone tissue implants, and cardiovascular implants. Combined with advanced 3D printing techniques, patient-specific or customized implants can be accessibly manufactured, easing the complexities of tissue regeneration and drug delivery.…”
Section: Present and Future Perspectivesmentioning
confidence: 99%